2004
DOI: 10.1038/sj.bjp.0706005
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the neuropeptide Y (NPY) contractile and relaxing receptors in horse penile small arteries

Abstract: 1 The distribution of neuropeptide Y (NPY)-immunorective nerves and the receptors involved in the effects of NPY upon electrical field stimulation (EFS)-and noradrenaline (NA)-elicited contractions were investigated in horse penile small arteries. 2 NPY-immunoreactive nerves were widely distributed in the erectile tissues with a particularly high density around penile intracavernous small arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…27 We have recently provided an explanation for this controversy between the rich presence of NPY-containing nerves in the penis and the lack of clear antierectile/vasoconstrictor effects of the peptide. 26 Thus, NPY was found to have a dual facilitatory/inhibitory role on the noradrenergic vasoconstriction of horse penile resistance arteries, the ability to enhance and decrease noradrenaline-induced contractions being achieved through a heterogenous population of NPY receptors. Both Y 1 -and Y 2 -postsynaptic receptors are involved in the NPY-induced enhancement of noradrenaline contractions, and presynaptic inhibitory Y 2 receptors limit noradrenaline release from (Figure 1).…”
Section: Physiological Regulation Of Penile Vasoconstrictionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 We have recently provided an explanation for this controversy between the rich presence of NPY-containing nerves in the penis and the lack of clear antierectile/vasoconstrictor effects of the peptide. 26 Thus, NPY was found to have a dual facilitatory/inhibitory role on the noradrenergic vasoconstriction of horse penile resistance arteries, the ability to enhance and decrease noradrenaline-induced contractions being achieved through a heterogenous population of NPY receptors. Both Y 1 -and Y 2 -postsynaptic receptors are involved in the NPY-induced enhancement of noradrenaline contractions, and presynaptic inhibitory Y 2 receptors limit noradrenaline release from (Figure 1).…”
Section: Physiological Regulation Of Penile Vasoconstrictionmentioning
confidence: 99%
“…20 Neuropeptide Y (NPY), a 36-amino acid peptide usually colocalized with noradrenaline in sympathetic perivascular nerves, is widely distributed in penile erectile tissues with a particularly high density around helicine arteries. 12,25,26 Although NPY was initially suggested to have a role in detumescence, 20 earlier in vitro studies showed either no effect of NPY in strips of human CC and cavernous artery or inconsistent contractions in penile circumflex veins. 4,12 Moreover, intracavernous injection of NPY increased intracavernous pressure and caused penile tumescence in rabbits.…”
Section: Physiological Regulation Of Penile Vasoconstrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-NPY antibody employed in this study was previously found to show specificity by preadsorption test in the horse urogenital system (Prieto et al, 1997(Prieto et al, , 2004. The immunogen utilized was synthetic porcine NPY (Table 1).…”
Section: Antibody Characterization Specificity Of Primary Antibodiesmentioning
confidence: 99%
“…penile arteries; calcium entry; nonselective cation channels; calcium sensitization PENILE ERECTION OCCURS when nitric oxide (NO) released from nerves and endothelium upon sexual stimulation relaxes smooth muscle of the corpus cavernosum (CC) and penile arteries, leading to blood filling of the sinuses and restriction of venous outflow (2, 25). During the flaccid state, erectile tissue is contracted by the release of neural and local factors, such as norepinephrine, neuropeptide Y, endothelin-1, and prostanoids that increase smooth muscle cytosolic Ca 2ϩ ([Ca 2ϩ ] i ) and/or Ca 2ϩ sensitization through activation G protein-coupled receptors (2,20,25). Erectile dysfunction (ED), considered as a sign of early endothelial dysfunction and cardiovascular disease, is three times more prevalent in men with Types 1 and 2 diabetes than in men without diabetes (3, 33).…”
mentioning
confidence: 99%